Dynamic skeletal muscle loss and its predictive role on 90-day mortality in patients with acute-on-chronic liver failure - Geng, Nan; Kong, Ming; Zhang, Jiateng; Xu, Manman; Chen, Huina; Song, Wenyan; Chen, Yu; Duan, Zhongping (Frontiers in Nutrition, 2025)
BackgroundLow skeletal muscle mass is an independent risk factor for increased mortality in patients with acute-on-chronic liver failure (ACLF). However, no study has evaluated the temporal changes in muscle mass during the course of ACLF. Therefore, this study aimed to investigate the dynamic changes in muscle mass and their prognostic role in patients with ACLF.MethodsA retrospective analysis was conducted on consecutive patients with ACLF who underwent two or more abdominal computed tomography examinations within 90 days of admission. The percentage change rates of the skeletal muscle index at the third lumbar vertebra (L3-SMI) were calculated as (L3-SMIfinal - L3-SMIinitial)/(L3-SMIinitial) × 100%.ResultsA total of 154 patients with ACLF were included. During the course of ACLF, the percentage change rates of L3-SMI at 2–7, 8–14, 15–30, 31–60, and 61–90 days were − 0.83 ± 4.43, −3.76 ± 4.40, −7.30 ± 5.89, −10.10 ± 7.45, and − 5.53 ± 9.26, respectively. Significant reductions in L3-SMI were noted in patients with severe conditions compared to other patients at 2–7 days and 15–30 days. Moreover, the rate of decrease in L3-SMI in patients with a lower respiratory quotient (RQ) was significantly greater than that in patients with a normal RQ at 2–7 days and 15–30 days. Additionally, high muscle loss (HR 2.059; 95% CI 1.122–3.780, p = 0.020), rather than pre-existing sarcopenia (HR 1.430; 95% CI 0.724–2.826, p = 0.303) at baseline, was independently associated with 90-day mortality.ConclusionDeterioration in muscle mass is associated with disease severity and poor nutritional status and serves as a more effective predictor of adverse short-term outcomes in patients with ACLF. These findings underscore the importance of dynamic evaluation of muscle loss and emphasize the necessity of reversing muscle loss in patients with ACLF.